The complementary benefit of anterior segment optical coherence tomography in penetrating keratoplasty - Yenerel NM (Dove Medical Press, 2013)
Nursal Melda Yenerel,1 Raciha Beril Kucumen,2 Ebru Gorgun3 1Haydarpasa Numune Research and Training Hospital, Istanbul, Turkey; 2Yeditepe University Medical Faculty, Department of Ophthalmology, Istanbul, Turkey; 3Dunya Goz Eye Hospital, Istanbul, Turkey Purpose: To evaluate the utility of anterior segment optical coherence tomography (AS-OCT) assessment in the pre- and postsurgical management of full-thickness corneal grafts. Methods: Seventy eyes of 58 patients who had penetrating keratoplasty were included in the study. High resolution AS-OCT scans of the cornea and the anterior segment were performed before and after transplantation in 17 eyes with the VisanteTM optical coherence tomography. Fifty-three eyes were examined in the late postoperative period. Results: The mean follow-up was 4.3 years (range, 1–15 years). Six different graft–host junctions were identified. Three patients with graft rejection, four patients with anterior synechia, and three patients with corneal ulcer were evaluated. Preoperative evaluation of eyes with semiopaque and totally opaque corneas revealed important information about anterior segment structures additional to slit-lamp findings. Conclusion: AS-OCT is a useful complementary tool for the evaluation of penetrating corneal transplantation surgery and in the management of its postoperative complications. Keywords: anterior segment optical coherence tomography, imaging techniques, penetrating keratoplasty